Design and Simulation of A Novel Piezoelectric AlN-Si Cantilever Gyroscope - Jian Yang; Chaowei Si; Fan Yang; Guowei Han; Jin Ning; Fuhua Yang; Xiaodong Wang (Micromachines, 2018)
A novel design of piezoelectric aluminum nitride (AlN)-Si composite cantilever gyroscope is proposed in this paper. The cantilever is stimulated to oscillate in plane by two inverse voltages which are applied on the two paralleled drive electrodes, respectively. The whole working principles are deduced, which based on the piezoelectric equation and elastic vibration equation. In this work, a cantilever gyroscope has been simulated and optimized by COMSOL Multiphysics 5.2a. The drive mode frequency is 87.422 kHz, and the sense mode frequency is 87.414 kHz. The theoretical sensitivity of this gyroscope is 0.145 pm/◦/s. This gyroscope has a small size and simple structure. It will be a better choice for the consumer electronics.